2005
DOI: 10.1002/ijc.21434
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of liquid‐based and conventional cytology in a South African screening trial

Abstract: Our study directly compares the performance of liquid-based (LBC) and conventional cytology for detecting high-grade cervical intraepithelial neoplasia and cancer (CIN 21) in high-risk, previously unscreened women. As part of a larger randomized clinical trial assessing the efficacy and safety of a ''screen and treat'' program for cervical cancer prevention, 5,652 South African women, aged 35 to 65 years, were screened using either ThinPrep or conventional Papanicolaou cytology. The cytology method used (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 31 publications
4
53
0
1
Order By: Relevance
“…Recent studies have challenged this notion, and to date, the question remains largely unanswered (20,70,71). A systematic review of 56 published studies that included over 1 million slides recently addressed the current literature on this subject (19).…”
Section: Conventional Pap Screening Versus Liquid-based Cytologymentioning
confidence: 99%
“…Recent studies have challenged this notion, and to date, the question remains largely unanswered (20,70,71). A systematic review of 56 published studies that included over 1 million slides recently addressed the current literature on this subject (19).…”
Section: Conventional Pap Screening Versus Liquid-based Cytologymentioning
confidence: 99%
“…In addition, the Bethesda system (TBS; 2001), which outlines cytological diagnostic criteria for cervical smears, is only gradually being adopted. It has been reported that the liquid-based cytology (LBC) method is useful for reducing the number of unsatisfactory specimens [1,2,3,4,5,6,7,8,9,10]. Unsatisfactory specimens are ≤1.1%, and one of the most common reasons for unsatisfactory specimens was too few squamous cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Unsatisfactory specimens are ≤1.1%, and one of the most common reasons for unsatisfactory specimens was too few squamous cells [11]. In addition, some reports have stated that the LBC method is associated with a higher cancer detection rate than the conventional method [1,8,12,13,14,15], whereas other reports found no difference between both methods [2,3,4,7,9,16,17,18,19,20]. According to meta-analyses and randomized studies, the number of unsatisfactory slides was not lower, or detection of high-grade lesions was not increased compared with conventional cytology [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Data from published SA studies suggest important regional differences and an increase in the prevalence of cytological abnormalities when compared with historical data. [3][4][5] Because of the low sensitivity of cytology, it can be assumed that the true prevalence of pre-invasive disease is underestimated by all available data. A single test of cervical cytology, even if optimal, will probably identify fewer than half of all existing pre-invasive cervical disease when measured against the greater yield obtained at colposcopy and directed biopsy.…”
mentioning
confidence: 99%